2019
DOI: 10.3122/jabfm.2019.06.190004
|View full text |Cite
|
Sign up to set email alerts
|

Accountable Care Organizations Serving Deprived Communities Are Less Likely to Share in Savings

Abstract: Primary care physicians are increasingly participating in accountable care organizations (ACOs). While prior studies have identified ACO and patient characteristics associated with savings, none have examined characteristics of the communities served by ACOs. Our objective was to assess the relationship between an ACO's service area characteristics and its savings rate. Methods: In this cross-sectional study, we used the Centers for Medicare and Medicaid Services 2014 Medicare Shared Savings Program ACO Provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Für die ACO bedeutet dies, dass sich Investitionen in die Population nicht zwingend rentieren. Auch verleitet diese Form der Zuordnung, Leistungserbringer mit Risiko-Populationen nicht in ACOs aufzunehmen [122].…”
Section: üBertragbarkeit Auf Deutschlandunclassified
“…Für die ACO bedeutet dies, dass sich Investitionen in die Population nicht zwingend rentieren. Auch verleitet diese Form der Zuordnung, Leistungserbringer mit Risiko-Populationen nicht in ACOs aufzunehmen [122].…”
Section: üBertragbarkeit Auf Deutschlandunclassified
“…For example, research on the hospital readmissions reductions program (HRRP) found safety net hospitals and those in underserved areas were more likely to receive penalties, and other research has found ACOs serving vulnerable populations have been less likely to earn shared savings. 11,28 As a result, providers serving clinically vulnerable populations, including older adults, may face difficulty meeting quality of care benchmarks, resulting in penalties for providers in disadvantaged communities. Penalizing providers and health systems caring for a higher need population can further impact their ability to care for patients and exacerbate health inequity.…”
Section: Refine Risk-adjustment To Reflect Social Risk Factorsmentioning
confidence: 99%
“…Despite good intentions, VBP models may negatively impact health equity without appropriate risk adjustment. For example, research on the hospital readmissions reductions program (HRRP) found safety net hospitals and those in underserved areas were more likely to receive penalties, and other research has found ACOs serving vulnerable populations have been less likely to earn shared savings 11,28 . As a result, providers serving clinically vulnerable populations, including older adults, may face difficulty meeting quality of care benchmarks, resulting in penalties for providers in disadvantaged communities.…”
Section: Vbp Model Design Features To Improve Health Equitymentioning
confidence: 99%
“…Care for disadvantaged individuals is also poorly reimbursed, which is likely not surprising to family physicians. Using large national datasets, Webb et al 23 report that Accountable Care Organizations serving the most deprived communities (as indicated by the Social Deprivation Index) are less likely to share in savings, receiving 2.3 percentage points lower shared savings than those serving the least deprived communities.…”
Section: Social Determinants Of Health-challenges To Best Medical Carmentioning
confidence: 99%